Information sharing for sales and operations planning: Contextualized solutions and mechanisms - Kaipia, Riikka; Holmström, Jan; Småros, Johanna; Rajala, Risto (Journal of Operations Management, 2017)
Abstract We develop actionable design propositions for collaborative sales and operations planning (S&OP) based on the observation of contexts in which benefits are generated — or are absent — from retail information sharing. An information sharing pilot project in a real‐life setting of two product manufacturers and one retailer was designed. The project resulted in one manufacturer, serving a retailer from its local factory, developing a process for collaborative S&OP, while the other manufacturer serving a retailer from more distant regional factories abandoned the process. The evaluation of the outcomes experienced by the two manufacturers allows us to examine contexts in fine‐grained detail and explain why introducing information sharing in the S&OP processes produce — or fail to produce — benefits. The paper contributes to the supply chain information sharing literature by presenting a field tested and evolved S&OP design for non‐standard demand situations, and by a contextual analysis of the mechanisms that produce the benefits of retailer collaboration and information sharing in the S&OP process.